The human condition of the nursing worker from the perspective of Hannah Arendt - Yanna Gomes de Sousa; Soraya Maria de Medeiros; Viviane Euzébia Pereira Santos; Rayrla Cristina de Abreu Temoteo; Jovanka Bittencourt Leite de Carvalho (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: This study intends to analyze how the human condition of the nurse is established in the context of Psychosocial Care Centers (Caps). Method: theoretical-reflexive study, anchored in three essential parts: 1) Theoretical and philosophical conception of the human condition from Hannah Arendt's perspective; 2) The nurse's work in the Caps; and 3) Human condition to think about the work of the nurse. Results: in the context of the Caps, the work can be represented by the psychic significations; the work, through the production of nurses' practice of care; and the action by the relations established between worker and institution, worker and user. Final considerations: the understanding of the vita activa allows to reflect on the human condition of the nurse in their work context and (re) considers a better understanding about the impact of the work on the life of these mental health workers in the contemporaneity.